A comparison of the increased temperature accelerated degradation of Poly(d, l-lactide-co-glycolide) and Poly(l-lactide-co-glycolide). (November 2020) - Geddes, L.; Carson, L.; Themistou, E.; Buchanan, F.
Abstract: Bioresorbable polymers composed of Poly(lactide), Poly(glycolide) and their related copolymers have become increasingly popular for the preparation of bone substitute constructs. In vitro tests assessing the degradative changes in physicochemical, mechanical, and biological properties of bioresorbable polymers are generally carried out at 37 °C, in pH 7.4 phosphate-buffered saline (PBS). However, long degradation times, varying from months to years make it difficult to assess these polymers at their late stages of degradation. An increased temperature accelerated degradation methodology, that simulates the long-term degradation of Poly( d, l -lactide- co -glycolide) and Poly( l -lactide- co -glycolide), has been validated in this study. Samples were degraded in PBS, under sterile conditions. Degradation temperatures of 47 °C, 57 °C and 70 °C were selected and compared to physiological temperature, 37 °C. At predetermined time intervals, samples were retrieved and evaluated for changes in mass, swelling, molecular weight, crystallinity, and thermal properties. The results from this study suggest that the degradation mechanism at elevated temperatures is similar to that observed at 37 °C. It is recommended that 47 °C is adopted by the research community to accelerate the degradation of these polymers. It is hoped the application of this methodology could be used as a valuable tool, prior to the assessment of the long-term biocompatibility of these polymers. Highlights: Validation of an accelerated degradation methodology for bioresorbable polymers. Proposal that accelerated degradation should be carried out at 47 °C. Degradation rate of Poly( d, l - lactide- co- glycolide) increased by ×4 at 47 °C compared to 37 °C. Degradation rate of Poly( l - lactide- co- glycolide) increased by ×22 at 47 °C compared to 37 °C.